Mathematical calculation of gamma rays interaction in bismuth gadolinium silicate glass using WinXCom program. (2022) - Chaiphaksa, W.; Borisut, P.; Chanthima, N.; Kaewkhao, J.; Sanwaranatee, N.W.
Abstract: The WO3 doped bismuth gadolinium silicate glass have been calculated using WinXCom program at the gamma energy range of 1 keV to 100 GeV in the concentration of WO3 = 0, 10, 20 and 30 mol%. The mass attenuation coefficient, the partial interaction and effective atomic number were investigated. The results of the photoelectric absorption, the μ m and the Z eff show the similar trend and the absorption edges were observed at an energy lower than 100 keV. The result can be found the photoelectric absorption at low photon energy, the Compton scattering in the medium photon energy and the pair production effect has the main interaction at high photon energy. Furthermore, the Z eff show increasing the concentration of WO3 the values because of the atomic number of W replacing Si in the glass matrix.